Japan's Future in East Asia and the Pacific - Pangestu, Mari (ANU Press, 2007)
Japan's Future in East Asia and the Pacific takes a 'big-picture' approach to Japan's economic place in East Asia alongside that of China. It analyses Japan's successes and experiments in trade policy as well as its failures in macro-economic policy. Japan's diplomatic and economic integration strategies are also examined for their impact on East Asia and on Australia. The collection assesses China's growth and dynamism and questions the nature of the competition for economic influence between Japan and China. Contributors to Japan's Future in East Asia and the Pacific are all graduates of The Australian National University who are making their mark in the region as scholars and economists on East Asian and Pacific affairs.